Human papillomavirus prevalence in the Irish cervical screening population and a specific group of HIV positive women - Mc Inerney, Jamie Kevin (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2011)
Human Papillomavirus (HPV) is the major aetiological agent in the development of cervical pre-cancer and cancer with high-risk HPV (HR-HPV) types 16 and 18 detected in greater than 70% of squamous cell carcinomas of the cervix. Expression of HPV oncoproteins E6 and E7 is necessary for development of malignancy. There is evidence to suggest that women with human immunodeficiency virus (HIV) have a higher prevalence of cervical pre-cancer and cancer. In this project, I aim to determine the prevalence and genotype distribution of HPV in two populations of women; the general cervical screening population and a subgroup of HIV positive women. I have determined a HR- HPV prevalence rate of 19.2% in the Irish cervical screening population (n=3193, median age 39.1, age range 17-89). HPV 16 was the most prevalent HPV genotype detected, followed by HPV 31/HPV 52, HPV 18, HPV 51 and HPV 39/HPV 66.
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin